Interpersonal Communication Among Single-Parent Fathers in Shaping Parenting on Social Development in Denai Village, Medan City - Pratama, Muhammad Imam; Subhani; Harinawati; Ali, Muhammad; Kamaruddin (CONTENT: Journal of Communication Studies, 2025)
Interpersonal communication plays a crucial role in parenting, especially for fathers who act as single parents. This study aims to explore how dyadic interpersonal communication between single fathers and their children shapes a parenting style that fosters social development in children living in Denai Subdistrict, Medan City. Using a qualitative approach with a descriptive method, data were collected through in-depth interviews, observations, and documentation. The research involved single fathers and their children as primary and additional informants to gain a comprehensive understanding of their communication dynamics. The findings indicate that dyadic interpersonal communication serves as the foundation for implementing a democratic parenting style. Fathers provide their children with the freedom to make independent decisions while offering guidance, support, and motivation. The communication pattern prioritizes openness, mutual understanding, and strong emotional support, allowing children to feel heard and valued. Furthermore, single fathers must assume multiple roles—not only as financial providers but also as caregivers who offer emotional and moral guidance. The ability to balance these responsibilities significantly impacts the child’s overall development. The success of this parenting approach is reflected in the child’s positive social growth, including their ability to engage with their surroundings, express empathy, and develop a sense of responsibility in everyday life. A structured and empathetic communication approach helps children build confidence and develop essential social skills. Therefore, this study emphasizes that interpersonal communication between single fathers and their children is not merely a parenting tool but also a crucial mechanism for shaping children's character and personality.